2020
DOI: 10.18632/aging.102705
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0070963 inhibits liver fibrosis via regulation of miR-223-3p and LEMD3

Abstract: Previous circular RNA (circRNA) microarray analyses have uncovered an abnormal expression of hsa_circ_0070963 in hepatic stellate cells (HSCs). However, the specific role of hsa_circ_0070963 in liver fibrosis remains unknown. Here, we show that hsa_circ_0070963 inhibits liver fibrosis via regulation of miR-223-3p and LEMD3. Moreover, we demonstrated that hsa_circ_0070963 levels were reduced during liver fibrosis while restoring hsa_circ_0070963 levels abolished HSC activation, with a reduction in α-SMA and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Currently, more and more circRNAs are identified to act as crucial regulators in multiple pathological and physiological processes of many types of disease. Previous studies have showed that circRNAs can regulate the activation and proliferation of HSCs by usually acting as miRNA sponges, thus to involve in the process of liver fibrosis in liver failure (Ji et al., 2020 ; Li et al., 2020 ). In this study, we first investigated that circDIDO1 overexpression could suppress the proliferation, reduced pro-fibrotic markers α-SMA and collagen I, and induced apoptosis as well as cell cycle arrest in HSCs, thus repressing HSC activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, more and more circRNAs are identified to act as crucial regulators in multiple pathological and physiological processes of many types of disease. Previous studies have showed that circRNAs can regulate the activation and proliferation of HSCs by usually acting as miRNA sponges, thus to involve in the process of liver fibrosis in liver failure (Ji et al., 2020 ; Li et al., 2020 ). In this study, we first investigated that circDIDO1 overexpression could suppress the proliferation, reduced pro-fibrotic markers α-SMA and collagen I, and induced apoptosis as well as cell cycle arrest in HSCs, thus repressing HSC activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mounting evidence shows the effect of circRNAs on HSC activation, which is essential for the pathogenesis of liver fibrosis. For example, hsa_circ_0070963 overexpression suppressed HSC activation with the reductions of collagen I and α-SMA by sponging miR-223-3p (Ji et al., 2020 ). Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al showed that expression profiles for hepatic circRNAs were significantly different between chronic hepatitis B (CHB) and normal hepatic tissues, with 99 dysregulated circRNAs identified in total 29 . Ji et al, reported the involvement of circ_0070963 in liver fibrosis 30 . Unexpectedly, this study did not reveal any significant association between circRNA expression and HBV, HCV, or cirrhosis status.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, hsa_circ_0007874 (cMTO1) could inhibit HSC activation through sponging miR-181b-5p and miR-17-5p [105,106]. Besides, hsa_circ_0070963 inhibits liver fibrosis via the regulation of miR-223-3p, which is related to HSC activation [107]. By targeting miR-18b-3p, circFBXW4 attenuates murine liver fibrogenesis with an anti-inflammation effect via inhibiting the activation and proliferation of HSCs, and inducing HSC apoptosis [108].…”
Section: Liver Fibrosis/cirrhosismentioning
confidence: 91%